The Tales of the Dayak Tribe: Values of Indonesian Cultural Character - Retna Ningsih (Universitas Indraprasta PGRI, 2022)
The many currents of foreign culture can fade the original culture of Indonesia. More specifically the culture of the Dayak tribe. The next generations have started to leave their original traditions and culture. Fairy tales are a culture that should be preserved, so that the longer it does not become extinct. This study aims to analyze the character values of the Dayak fairy tales on the island of Borneo. In addition, the research also describes the social value in the story. Dayak fairy tales can instill education in their descendents. The research method uses descriptive qualitative methods. The data is taken from a collection of fairy tales from Tanah Dayak, by Essau Albert Menggang. The results showed that the Dayak fairy tales contain character and social values that can be used as a forum and educational tool for today's young generation. The composition of the character values in the fairy tales from Tanah Dayak are 13% religius values, 9% hard work, 9% respect for others (social), 5% peace-loving, 13% independent, creative as much as 9%, caring as much as 37%, and discipline as much as 5%. From this analysis, it is necessary for the next generation to be able to use fairy tales as a means of education that comes from Indonesian culture.Keywords: Put 3-5 your keywords here; keywords separated by semicolon.